PENGARUH DIREKTUR WANITA, TATA KELOLA, DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - REYNA EDITA; YOSEPH ANASTASIUS DIDIK CAHYANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to provide empirical evidence about the effect of female directors, institutional ownership, managerial ownership, audit committee meetings, independent commissioners, firm size, leverage, firm age, audit quality, and return on asset on earnings management. Samples of this research were selected based on the purposive sampling method and resulted in 110 nonfinancial companies listed on Indonesia Stock Exchange during the period of 2017-2019. The data obtained from these samples were analyzed using multiple regression analysis on SPSS 25. The results of this research show that leverage has effect on earnings management, while female directors, institutional ownership, managerial ownership, audit committee meetings, independent commissioners, firm size, firm age, audit quality, and return on asset have no effect on earnings management